Randomised clinical trial: the 5‐HT4 agonist revexepride in patients with gastro‐oesophageal reflux disease who have persistent symptoms despite PPI therapy. Issue 7 (19th February 2015) - Shaheen, N. J.; Adler, J.; Dedrie, S.; Johnson, D.; Malfertheiner, P.; Miner, P.; Meulemans, A.; Poole, L.; Tack, J.; Thielemans, L.; Troy, S.; Vakil, N.; et al.
Summary: Background: A substantial proportion of patients with gastro‐oesophageal reflux disease (GERD) have only a partial response to proton pump inhibitor (PPI) therapy. Prokinetic drugs may improve reflux symptoms by enhancing oesophageal motility and gastric emptying. Aim: To evaluate the effect of revexepride, a novel prokinetic 5‐hydroxytryptamine type 4 (5‐HT4 ) receptor agonist, compared with placebo, in patients with GERD who have a partial response to PPIs. Methods: A phase 2b, double‐blind, parallel‐group study was conducted, in which patients were randomised to one of three revexepride treatment groups (0.1, 0.5 and 2.0 mg three times daily) or placebo (1:1:1:1 ratio). Daily e‐diary data captured patients' symptoms over an 8‐week treatment period. The primary efficacy outcome was the weekly percentage of regurgitation‐free days in the second half of the study (weeks 5–8). Results: In total, 480 patients were randomised and 477 received treatment (mean age 47.9 years; 61% women). The mean percentage of regurgitation‐free days increased from baseline (range, 15.0–18.8%) to week 8 (62.3–70.5%) in all four study arms; however, there were no statistically significant differences in this change between placebo and the three treatment arms. No dose‐dependent relationship in treatment effect was observed for any of the study endpoints. The incidence of treatment‐emergent adverse events (TEAEs) was revexepride dose‐dependent. Only one serious TEAE occurred and none resulted in death. Conclusions: Revexepride was no more effective than placebo in controlling regurgitation in patients with GERD symptoms partially responsive to PPIs. Revexepride was well tolerated.ClinicalTrials.gov Identifier: NCT01472939.